Respon Tanaman Melon (Cucumis melo L.) Terhadap Waktu Pemangkasan Tunas dan Interval Pemberian Urine Kelinci - Charles Samo Langobiri; I Ketut Irianto; Anak Agung Ngurah Mayun Wirajaya (Fakultas Pertanian, Universitas Warmadewa, 2019)
This research was conducted on 20 March to 15 June 2018. Aiming to find out the response of plant melon (Cucumis melo L). The design used in this study was a Randomized Block Design (RBD) which consists of two factors. IE: pruning Treatment consists of three levels, namely: P1 (trimming 1 week after planting), P2 (trimming 2 weeks after planting), P3 (the 3 trimming after planting). Treatment interval of the giving of the rabbit urine consists of 4 levels, namely: U0 (unannounced), U2 (3 days), and U3 (6 days). U4 (9 days). Thus there are 12 treatment combinations and each treatment was repeated three times so that there are 36 pot experiment. esearch results indicate that the interaction between treatment and trimming the interval of granting influential rabbit urine not real against all variables were observed. P3 gives the amount of pruning treatment of branches per plant increased with branch 16.25 highest 25% when compared to the number of branch lowest branch at the time of 13.00 i.e. pruning of P1. Pruning treatment gives the highest total solids solution P1 15.58 Í¦ brix with increased 10.73% compared with lowerst total solids solution i.e. 14.07 Í¦ brix at the time the pruning of P3. While on the treatment interval rabbit urine U2 the highest value in the variable weight of fresh fruit per plant that is 984.87 (g) and lowest at the treatment the U3 with the value of the different g 883.33 unreal with U1 and U0 treatment each value that is 943.78 g and 889.39 g.